Why Rights? A Commentary on Malte-Christian Gruber. Issue 2 (3rd May 2020) - Menke, Christoph
Abstract: Malte-Christian Gruber has called for an extension of the concept of rights to living beings and artifacts in order to recognize them "as independent legal subjects." As Gruber notes, this implies the dissolution of the unity of legal and political subjectivity; the extension of rights is the de-politicization of rights. While the unity of legal and political subjectivity formed the emancipatory claim of the modern discourse of rights, the form of rights could in fact never redeem this claim. This suggests, however, that the form of rights should not be extended ever further to new bearers and contents, but that this form as such should be questioned.